Resiliensi mahasiswa perantau : Bagaimana peranan dukungan sosial? - Tzanilfanid Dhuha; Isrida Yul Arifiana; Suroso (INNER: Journal of Psychological Research, 2023)
The purpose of this research is to identify and analyze the relationship between social support and the resilience of overseas students in the city of Surabaya. This research is a quantitative correlational study with overseas student subjects used as samples, namely active student status, aged 17 to 24 years, coming from outside the city of Surabaya who currently resides in Surabaya and do not live with their parents. The sampling technique used in this study was accidental sampling, meaning that anyone the researchers met with the appropriate criteria could become a sample. The number of samples in this study were 107 respondents. Measuring tools used are social support scale and resilience scale. The results showed that there was a very significant positive relationship between social support and the resilience of overseas students. So, the higher the social support received by overseas students, the higher the level of resilience.